The prognostic role of vasculoendothelial growth factor A in patients with ST-segment elevation acute myocardial infarction during 6-months follow-up period - N.P. Kopytsya; I.M. Кutya; I.V. Rodionova; Ya.V. Hilova (Кардіохірургія та інтервенційна кардіологія)
The aim – to evaluate the prognostic role of vasculoendothelial growth factor A (VEGF-A) in patients with ST segment elevation acute myocardial infarction (STEMI) after successful revascularization during the 6-month follow-up period.